Analyzing the Influence of Quality, Price, and After-Sales Service of 5 Sedan Low Category to Consumer Satisfaction - Dwi Irawati; Yuni Siti Nuraeni (Komunitas Dosen Indonesia, 2020)
The demand for private transportation that comfort, cheap, and good quality has been increasing lately. It caused many companies to launch any car that can answer the request. Refer to Indonesia, people that like most to visit each other and traveling created an increasing demand for this type of car. The Indonesian automotive market launch type of car that has a sedan category but has a small shape, it called the city car. City car has answered the demand for many consumers especially for a little family with two or more children who want to have a small vehicle completed with comfort, cheap and excellent quality features so that my research is to proof is there any relation between quality, price and after-sales service according to consumer satisfaction to 5 best seller refer to web otomotif.kompas.com, they are Toyota Agya, Daihatsu Ayla, Honda Brio Satya, Suzuki Wagon R15 dan Datsun GO+. The result of this research is proving that quality, price, and after-sales service has a connection to consumer satisfaction